Shopping attributes towards tourists revisit intention to Melaka / Hazeera Hafezah, Noorhashimah E Rahman and Nurliyana Syazwani Zulkefli - Hafezah, Hazeera; E Rahman, Noorhashimah; Zulkefli, Nurliyana Syazwani (Faculty of Hotel and Tourism Management, 2013)
Shopping is an increasingly important leisure and tourist activity. Shopping becomes the most common and enjoyable activities undertaken by the people when they are on holiday. It is also acknowledged as a primary means of generating tourism revenue and contributing to economic development. In Malaysia, shopping is the country's second highest contributor where the shopping activities alone accounted as much as 25.7% of the tourist total expenditure in 2006. For that reason, this paper aims to highlight the attributes of shopping towards tourist’s revisit intention to Melaka. The results in this study provide strong support for the propositions of the study that five of the shopping attributes (quality of customer service, convenience, shopping environment, quality of the retailers and rewards and discounts) have significant influential effects on tourist’s revisit intention. The study found that both the shopping environment and rewards and discount were having the most significant contribution on the tourist’s revisit intention. Hence, the shopping environment as such the spaciousness, trendy, and cleanliness is essential factors to the tourist’s revisit intention. Furthermore, the availability of discounts in most shopping centers especially during sales and promotion and festivals are the extra bonus in creating tourist’s intention to revisit.